2007
DOI: 10.1177/230949900701500209
|View full text |Cite
|
Sign up to set email alerts
|

Medial Humeral Epicondylar Fracture in Children and Adolescents

Abstract: Purpose. To assess treatment outcomes of young patients with medial epicondylar fracture of the elbow using standard operative protocols. Methods. 24 consecutive patients with medial humeral epicondylar fracture underwent surgery by one of the 3 methods: (1) 2 parallel Kirschner wires, (2) 2 parallel Kirschner wires plus a tension-band wire, and (3) a screw plus an anti-rotation Kirschner wire. Fractures displaced less than 5 mm were treated conservatively (casting for 3 weeks). Outcome was assessed clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 4 publications
2
29
1
1
Order By: Relevance
“…Five studies had patients treated only with operative means [6, 7, 108, 109, 114]. Operative treatments included Kirschner wires [57, 10, 12, 108110, 112114], screw fixation [5, 7, 12, 109, 111, 112, 114], suture [5, 12, 109–111], excision of the fragment and suturing of the soft tissue to the periosteum of the medial elbow [10], tension band wiring [109, 112], Palmer pins [7, 110], closed reduction and percutaneous pinning [6], or open reduction alone [3]. In total, 321 patients received some type of operative treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies had patients treated only with operative means [6, 7, 108, 109, 114]. Operative treatments included Kirschner wires [57, 10, 12, 108110, 112114], screw fixation [5, 7, 12, 109, 111, 112, 114], suture [5, 12, 109–111], excision of the fragment and suturing of the soft tissue to the periosteum of the medial elbow [10], tension band wiring [109, 112], Palmer pins [7, 110], closed reduction and percutaneous pinning [6], or open reduction alone [3]. In total, 321 patients received some type of operative treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Two studies performed surgery when the medial epicondyle fracture was associated with dislocation of the humero-ulnar joint [113, 114]. Four studies performed surgery on significantly displaced fractures [11, 108, 112, 113], though significant displacement was variable in its definition. One used ulnar nerve symptoms as an indication for surgery [108].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have reported favourable outcomes with surgical treatment of displaced medial epicondyle fractures, particularly in avoiding radiological nonunion and valgus instability of the elbow [9][10][11][12][13]16,17]. However, several other studies have shown that nonoperative treatment can yield good long-term functional results, and that surgical intervention is not necessarily indicated even if fracture displacement is greater than 5 mm [3,5,7].…”
Section: Discussionmentioning
confidence: 97%
“…There has been hitherto no consensus on what constitutes 'significant' displacement. Displacements of greater than 2, 5 or 10 mm have been used as the threshold for surgical fixation in different studies; 5 mm seems to a frequently used cut-off [3,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Another avulsion injury consists of purely muscular avulsion secondary to contraction of the forearm fl exors when the elbow is fl exed. This mechanism may be responsible for medial epicondylar fractures associated with arm wrestling and overhead throwing [ 22 ]. A displaced bony fragment can injure the ulnar nerve, which passes through a groove in the posterior aspect of the medial epicondyle.…”
Section: Imagingmentioning
confidence: 97%